AN ANALYSIS OF READABILITY LEVEL OF READING MATERIAL IN ENGLISH TEXTBOOK FOR FIRST GRADE OF SENIOR HIGH SCHOOL - Yetti, Dzulhijjah (Journal of Education and Teaching, 2021)
Predicting readability level of reading texts can help the teachers to match the texts with student’s grade. The appropriate reading text is expected to ease the students in comprehending the material. This research focused on the readability level of English reading material found in English textbook entitled Bahasa Inggris for first grade of Senior High School Published by Curriculum and Books Center, Research and Development Agency, Ministry of Education and Culture. This study attempts to find out whether the reading materials are appropriate or not in terms of readability level for the target students. This research used descriptive quantitative design. The object of the research is English textbook entitled Bahasa Inggris for First Grade of Senior High School published by Curriculum 2013. The textbook consists fifteen chapters which contained kinds of reading materials such as dialogue and reading texts. The researcher only focuses on analyzing the reading materials. There are three kinds of genre found in this book, they are descriptive, recount and narrative. The data were collected by using document analysis. In calculating readability level, the researcher employed the Flesch Reading Ease (FRE) formula. The results of the study showed that there were 9 reading texts in the Bahasa Inggris textbook. From those 9 texts found that there were 3 descriptive texts, 4 recount texts, and 2 narrative texts. According to the analysis using Flesch Reading Ease (FRE) formula, the researcher found that there were 3 texts in Fairly Easy level, 3 texts in Fairly Difficult level, and 3 texts in Difficult level. In average, the texts are in Fairly Difficult level (57,3). Based on the theory of Flesch Reading Ease (FRE) formula, it is found that the texts are in the appropriate level for tenth grade students.Keyword: Readability level, Reading Material, Textbook.